KEWENANGAN PENGUJIAN PERATURAN PERUNDANG-UNDANGAN (Analisis Perbandingan Antara Negara Indonesia Dengan Negara Prancis) - Annisa Hidayatush Sholikha; Ismail Hasani; Fathudin Fathudin (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
This study describes comparison problems of Judicial Reviews in Indonesia and France. Which is where in the comparison, there is an equation and Judicial Review of the Prevailing Laws. This study aims to determine the development of the Judicial Review in Indonesia and French. In particular, this thesis explores a method of Judicial Review between Indonesia and France. The results show that, in Indonesia, there are two institutions that carry out Judicial Review, namely the Supreme Court and the Constitutional Court. This is the basis for the comparison of Judicial Review with the French state, which in the French state is only carried out with one institution, namely the Constitutional Council. In general, the practice of Constitutionality contains various aspects such as institutional aspects, procedures and the nature of the decision. In the institutional context, a special institutionalization model is to form an institution such as the Constitutional Court in Indonesia. Then a model of testing by establishing a new body specifically but having a political character and not a judicial body was found in France with the Conseil Constitutionnel. The existence of a Constitutionality Review agency has implications for the procedural aspects and forms of testing it.